A physiological comparison of the new—over 70 years of age—marathon record holder and his predecessor: A case report - Van Hooren, Bas; Lepers, Romuald (Frontiers in Physiology, 2023)
Purpose: This study assessed the body composition, cardiorespiratory fitness, fiber type and mitochondrial function, and training characteristics of a 71-year-old runner who broke the world record marathon of the men’s 70-74 age category and held several other world records. The values were compared to those of the previous world-record holder. Methods: Body fat percentage was assessed using air-displacement plethysmography. V̇O2max, running economy, and maximum heart rate were measured during treadmill running. Muscle fiber typology and mitochondrial function were evaluated using a muscle biopsy. Results: Body fat percentage was 13.5%, V̇O2max was 46.6 ml∙kg-1∙min-1, and maximum heartrate was 160 beats∙min-1. At the marathon pace (14.5 km∙h-1), his running economy was 170.5 ml∙kg-1.km-1. The gas exchange threshold and respiratory compensation point occurred at 75.7% and 93.9% of the V̇O2max, i.e., 13 km∙h-1 and 15 km∙h-1, respectively. The oxygen uptake at the marathon pace corresponded to 88.5% of V̇O2max. Vastus lateralis fiber content was 90.3% type I and 9.7% type II. Average distance was 139 km∙w-1 in the year prior to the record. Conclusion: The 71-year-old world-record holder marathon showed a relatively similar V̇O2max, lower percentage of V̇O2max at marathon pace, but a substantially better running economy than his predecessor. The better running economy may result from an almost double weekly training volume compared to the predecessor and a high type I fiber content. He trained every day in the last ~1.5 years and achieved international performance in his age group category with a small (<5% per decade) age-related decline in marathon performance.